DEATH CRIME IMPOSITION CONTROVERSY IN INDONESIA: KONTROVERSI PENJATUHAN PIDANA MATI DI INDONESIA - Waruwu, Sulasri (LPPM UPMI, 2023)
This study aims to analyze the controversy over the imposition of death penalty and its application. The research method used in this study is a type of normative research with a statutory approach (Statute Approach). The results of this study state that until now, the imposition of death penalty is still a prolonged polemic. This is because both parties who are pro or con against this type of crime both rely on their opinions with logical and rational reasons. In fact, it would not be such a controversial issue if the implementation has definite stages and has permanent legal force and is followed by reforming the legal system. As for suggestions addressed to the government (in this case the legislators) so that even though the death penalty is still maintained in Indonesian positive law, on the contrary it still pays attention to aspects of legal protection and the convict's right to life.